Preclinical Animal Models for Q Fever Vaccine Development - Tesfamariam, Mahelat; Binette, Picabo; Long, Carrie Mae (Frontiers in Cellular and Infection Microbiology, 2022)
Coxiella burnetii is a zoonotic pathogen responsible for the human disease Q fever. While an inactivated whole cell vaccine exists for this disease, its widespread use is precluded by a post vaccination hypersensitivity response. Efforts for the development of an improved Q fever vaccine are intricately connected to the availability of appropriate animal models of human disease. Accordingly, small mammals and non-human primates have been utilized for vaccine-challenge and post vaccination hypersensitivity modeling. Here, we review the animal models historically utilized in Q fever vaccine development, describe recent advances in this area, discuss the limitations and strengths of these models, and summarize the needs and criteria for future modeling efforts. In summary, while many useful models for Q fever vaccine development exist, there remains room for growth and expansion of these models which will in turn increase our understanding of C. burnetii host interactions.